Endoscopic Drainage of Pancreatic Pseudocysts: Clinical Profile and Outcome Analysis - Gurung, Ram Bahadur; Sharma, Pasand; Sapkota, Prakash; Shrestha, Ashish; Shrestha, Pramita (Journal of Nepal Health Research Council, 2024)
Background: Pancreatic pseudocyst is a complication of acute and chronic pancreatitis. Although surgery considered the gold standard, there is a rapid shift towards endoscopic treatment owing to its therapeutic outcome and minimal invasive involvement. This study aims to present the clinical profile and outcome analysis of the endoscopic drainage of pancreatic pseudocysts in Dhulikhel Hospital. Methods: This is a retrospective review of all patients who were diagnosed with pancreatic pseudocyst between January 2015 and December 2018 in Dhulikhel Hospital. The retrospective data were on patient characteristics, etiology, location of the cyst, other clinical characteristics. Results: The study included 51 patients and the average age of the patients in this study was 39 years and among them 62.7% were female. The mean size of pseudocyst was 7.89 cm, and the average days of hospital stay was 13.64. The most common etiology was idiopathic and more than half of the patient’s cyst was in head and/or body, 15 and 36 underwent conservative and therapeutic management respectively. The technical success rate was at 94% and reported increased pancreatic pseudocyst in Dhulikhel Hospital from 2015-18. Conclusions: The study findings highlight the increased trend of pancreatitis pseudocyst as a complication of acute or chronic pancreatitis. Endoscopic drainage of pseudocyst with plastic stent is an established method of managing it. However, pancreatic pseudocyst even larger than 6 cm can undergo spontaneous resolution.Hence, conservative management should be considered first. Keywords: Endoscopic ultrasound; endoscopic drainage; pancreatitis; pancreatic pseudocyst.